Enhancing EFL Undergraduate Students’ Speaking Fluency through Chunking - Monica Monica (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2022)
The objective of this research is to examine the impact of using chunking, multiword groups, on enhancing EFL Undergraduate students' speaking fluency. As a learner of English as a foreign language, the obstacle experienced in improving productive skills, especially in speaking such as fluency in speaking with minimal understanding of the importance of understanding how the native speaker uses many chunks in communicating fluently. In the initial stage of this research, students in the same class of speaking in general speaking skills through speaking skills tests and interviews in English to measure their general speaking skills in the same population. Furthermore, the class was divided into two large groups, control and experimental groups using the same material and speaking skills. However, the experimental group was given learning and practice using chunking to improve their fluency in speaking. In the final stage, the second group was given a posttest in the form of an interview with the same material to measure the difference in their level of speaking ability, especially the frequency of using chunking in speaking fluency. The findings showed a significant difference in increasing speaking fluency in the experimental group and positive attitudes towards the use of chunking in enhencing speaking fluency.